THE SPATIAL COMPOSITION OF ALUN-ALUN ON JAVA ISLAND TODAY - Takako Kohori; Akhmad Arifin Hadi; Katsunori Furuya (TATALOKA, 2019)
This study focuses on alun-alun, the open spaces in Indonesia that have a long cultural history. Alun-alun mostly located in the center of cities; they influence the pattern of cities and become a mental map for inhabitants. In this study, we investigated the distribution of alun-alun throughout Java Island. The research consisted of three parts. First, we identified Alun-alun from the colonial era using the old maps from Leiden University There were 15 locations of alun-alun in 13 cities identified from the old maps with characteristics as follows; 1) rectangular land, 2) located adjacent to the city mosque, and 3) located adjacent to the Regent’s office or Palace. In the second part, from those definitions, we confirmed 90 locations of alun-alun in 87 cities that have existed from the colonial period to the present across Java Island. The third part, we clarified the current province of alun-alun from two perspectives: area and spatial composition. We found that the present alun-alun show regional tendencies. Alun-alun in cities of Banten and West Java province was mostly in a small-scale area without Ficus benjamina trees. These points overlap with features described in the colonial era. Alun-alun in cities of Central Java and Yogyakarta province was relatively in a large-scale area and characterized by Ficus benjaminaas the main tree. Alun-alun in cities of East Java province was also in a large-scale area, but space mostly divided by planted areas, open area, structures, and others.